Phenotypic and molecular analyses of primary lateral sclerosis. (June 2015) - Mitsumoto, Hiroshi; Nagy, Peter L.; Gennings, Chris; Murphy, Jennifer; Andrews, Howard; Goetz, Raymond; Floeter, Mary Kay; Hupf, Jonathan; Singleton, Jessica; Barohn, Richard J.; Nations, Sharon; Shoesmith, Christen; et al.
Abstract : Objective: To understand phenotypic and molecular characteristics of patients with clinically "definite" primary lateral sclerosis (PLS) in a prospective study. Methods: Six sites enrolled 41 patients who had pure upper motor neuron dysfunction, bulbar symptoms, a normal EMG done within 12 months of enrollment, and onset of symptoms ≥5 years before enrollment. For phenotypic analyses, 27 demographic, clinical, and cognitive variables were analyzed using the k-means clustering method. For molecular studies, 34 available DNA samples were tested for the C9ORF72 mutation, and exome sequencing was performed to exclude other neurologic diseases with known genetic cause. Results: K-means clustering using the 25 patients with complete datasets suggested that patients with PLS can be classified into 2 groups based on clinical variables, namely dysphagia, objective bulbar signs, and urinary urgency. Secondary analyses performed in all 41 patients and including only variables with complete data corroborated the results from the primary analysis. We found no evidence that neurocognitive variables are important in classifying patients with PLS. Molecular studies identified C9ORF72 expansion in one patient. Well-characterized pathogenic mutations were identified in SPG7, DCTN1, and PARK2 . Most cases showed no known relevant mutations. Conclusions: Cluster analyses based on clinical variables indicated at least 2 subgroups of clinically definite PLS. Molecular analyses further identified 4 cases with mutations associated with amyotrophic lateral sclerosis, Parkinson disease, and possibly hereditary spastic paraplegia. Phenotypic and molecular characterization is the first step in investigating biological clues toward the definition of PLS. Further studies with larger numbers of patients are essential.